Improving physical activity, mental health outcomes, and academic retention in college students with Freshman 5 to thrive: COPE/Healthy lifestyles. Issue 6 (18th June 2013) - Melnyk, Bernadette; Kelly, Stephanie; Jacobson, Diana; Arcoleo, Kimberly; Shaibi, Gabriel
Abstract Purpose To assess the preliminary effects of a new course entitled Freshman 5 to Thrive/COPE Healthy Lifestyles on the cognitive beliefs, knowledge, mental health outcomes, healthy lifestyle choices, physical activity, and retention of college freshmen. Data sources Measures included demographics, nutrition knowledge, healthy lifestyle beliefs, healthy lifestyle perceived difficulty, healthy lifestyle choices, Beck Youth Inventories‐II (anxiety, depression, anxiety, and destructive behavior), step count via pedometer, and college retention. Conclusions The experimental COPE (Creating Opportunities for Personal Empowerment) group had greater intentions to live a healthy lifestyle (p = .02) versus the comparison group. COPE students also significantly increased their physical activity (p = .003) from baseline to postintervention and had a higher college retention rate than students who did not take the course. In addition, there was a significant decrease in depressive and anxiety symptoms in COPE students whose baseline scores were elevated. Implications for practice The Freshman 5 to Thrive Course is a promising intervention that can be used to enhance healthy lifestyle behaviors and improve mental health outcomes in college freshmen.